Gamma ray inactivation of some animal viruses. - Thomas, F C (1981)
Twenty samples of animal viruses comprising 14 different viruses in 12 families were subjected to varying doses of gamma irradiation from a 60Co source in a Gamma Cell 220 (Atomic Energy of Canada Limited) to determine lethal dose levels. The dose responses appeared linear throughout inactivation. The D10 values, that is the dose necessary to reduce infectivity by one log10, ranged from less than 0.20 Megarads to approximately 0.55 Megarads. There was not a complete inverse correlation between the target size (virion core) and the D10 value.